2016
DOI: 10.4085/110127
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Athletic Training Students That Preceptors Find Desirable

Abstract: Context: Athletic training students acquire clinical hours under the direct supervision of athletic training preceptors. Objective: The purpose of this project was to explore what characteristics preceptors desire in their athletic training students. Design and Setting: Online survey instrument. Patients or Other Participants: A total of 286 certified athletic trainers (128 male, 158 female; average years experience 10.58 ± 8.48). Participants were required to be cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Empathy is the ability to accurately perceive and understand the emotional state of others, by means of putting yourself in another's shoes and/or relying on a previous personal experience (Carr et al, 2016). Preceptors showed that they would understand difficulties and problems new nurses face in their workplace.…”
Section: Empathymentioning
confidence: 99%
“…Empathy is the ability to accurately perceive and understand the emotional state of others, by means of putting yourself in another's shoes and/or relying on a previous personal experience (Carr et al, 2016). Preceptors showed that they would understand difficulties and problems new nurses face in their workplace.…”
Section: Empathymentioning
confidence: 99%